KUALITAS PELAYANAN PUBLIK PADA MASA PANDEMI COVID-19 DI KANTOR PENGADILAN NEGERI KENDARI SULAWESI TENGGARA - Sartono Sartono; Erni Qomariyah; Ayufi Jufri (Universitas Halu Oleo, 2022)
This study aims to determine the quality of public services during the Covid-19 pandemic. This research is descriptive qualitative research, with data collection techniques, namely observation, interviews, and documentation studies. The technique used is purposive sampling. The data has been obtained and analyzed using qualitative data analysis techniques. The results of this study show that the quality of public services during the Covid-19 pandemic at the Kendari District Court Office Class 1A has been very good and effective. In general, the service recipients are already happy with the services provided, but there are still some complaints from the visitors themselves because employees who are working from home (WFH) are not in the office. The Kendari District Court Office carried out services during the Covid-19 pandemic, strictly complying with health protocols from wearing masks, ensuring clean work areas, providing hand washing stations, providing hand sanitizers, and taking temperature measurements. The service went well because all employees in the office followed health guidelines, even every employee was given vitamins and bear milk, conducted swab tests, and vaccinated so that the health of the employees was maintained.